2022
DOI: 10.3390/microorganisms10091871
|View full text |Cite
|
Sign up to set email alerts
|

Pep27 Mutant Immunization Inhibits Caspase-14 Expression to Alleviate Inflammatory Bowel Disease via Treg Upregulation

Abstract: Inflammatory bowel disease (IBD) is a highly prevalent gut inflammatory disorder. Complicated clinical outcomes prolong the use of conventional therapy and often lead to compromised immunity followed by adverse events and high relapse rates. Thus, a profound medical intervention is required. Previously, intranasal immunization of pneumococcal pep27 mutant (Δpep27) exhibited long-lasting protection against immune-related disorders. System biology analysis has predicted an inverse correlation between Δpep27 immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Additionally, SCFA are known to limit mucosal inflammation by the induction of Tres [24]. Our findings indicates that microbiota composition in Δpep27-immunizaed colitis mice showed positive correlations with the Treg induction and negative association with the proinflammatory cytokines [25].…”
Section: Lung-gut Axismentioning
confidence: 55%
See 2 more Smart Citations
“…Additionally, SCFA are known to limit mucosal inflammation by the induction of Tres [24]. Our findings indicates that microbiota composition in Δpep27-immunizaed colitis mice showed positive correlations with the Treg induction and negative association with the proinflammatory cytokines [25].…”
Section: Lung-gut Axismentioning
confidence: 55%
“…During our approach to intranasal immunization using Δpep27 for prevention of pneumococcal diseases, microarray and system biology analyses of human lung cells after a Δpep27 infection unraveled unexpected features predicting preventive effect of influenza virus infection and intestinal abnormality. Thereafter, a series of experiments on this prediction were performed and show that the prediction is true [25,36,37].…”
Section: Intranasal Immunization Of δPep27 Protects Against Pathogens...mentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-14 belongs to caspase family that is related to apoptosis. Many previous studies have shown that caspase has an important effect on pathology of various disorders, like retinal dysfunction and multiple malignant tumors [33][34].…”
Section: Discussionmentioning
confidence: 99%